(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
Study of the history of lexical structure of Ukrainian language is impossible without finding out the history of some semantic groups. Analysis of the word-building nests with odorativnymi roots (in the dictionary "-Latin Lexicon of Glory" Slavinetsky E. and A. Koretsky-Satanovsky) is the smell in the vocabulary of Ukrainian language in the seventeenth century.